(untitled) (NTU Journal of Agriculture and Veterinary Science, 2025)
The research was conducted on the Animal Production field of the College of Agriculture and Forestry / University of Mosul. Twenty-four Awassi lambs were used in study, randomly divided into four treatments. The lambs of the first treatment (control), were fed the standard diet only, while the lambs of the second, third, and fourth treatments, were fed the standard diet with the addition of 25, 50, and 75 g/kg olive leaves powder, respectively. The study lasted for 90 days, preceded by an introductory period that lasted for 10 days. At the end of the study, three lambs from each treatment, were slaughtered to study carcass characteristics. The results of the statistical analysis of live body weight showed that there was a significant superiority (P?0.05) for all three olive leaves treatments, and the significant superiority was reflected in the hot carcass weight, and all treatments did not differ significantly in the dressing percentage relative to the hot carcass weight. The results of the physical dissection of the three ribs (9, 10, and 11), showed that there was a significant increase (P?0.05) in ribs weight, rib eye area and ribs fat for all olive leaves treatments. While the bone weight of the three ribs decreased significantly in the second and third olive leaves treatments, lean weight increased significantly in 2nd and 4th treatments. Wide tail fat and kidney fat increased significantly in all olive leaves treatments, also recorded a significant increase in Omental and Mesenteric fat in 3rd and 4th treatments. The addition of olive leaves to the ration of Awassi lambs cased an improvement in body and carcass weight and some carcass traits.